Responses of Nasal Polyp-Derived Macrophages to Inflammatory Cues and Potential Pathological Roles in Type 2 Chronic Rhinosinusitis With Nasal Polyps - Hyunkyung Cha; Ara Jo; Hee-Suk Lim; Kyoung Mi Eun; Jin-A Park; Seung-No Hong; Dae Woo Kim (Clinical and Experimental Otorhinolaryngology, 2026)
Objectives. The role of highly plastic and heterogeneous macrophages in the pathogenesis of nasal polyps (NP) is not well understood. We aimed to investigate the distribution and responses of NP-derived macrophages to inflammatory cues according to endotypes of chronic rhinosinusitis with nasal polyps (CRSwNP).Methods. The distribution of macrophage subsets was analyzed using NP bulk RNA sequencing data with CIBERSORTx program. The cytokines and chemokines produced by NP-derived macrophages following stimulation with interleukin (IL)-4, staphylococcal enterotoxin B (SEB), and lipopolysaccharide were evaluated using a multiplex cytokine assay. Immunofluorescence staining in NP tissues was conducted to validate the findings.Results. Type 2 CRSwNP exhibited a significantly higher proportion of M2 macrophages, whereas both M1 and M2 macrophage populations were elevated in non-type 2 CRSwNP. Baseline cytokine analysis of NP-derived macrophages revealed an increase in thymic stromal lymphopoietin (TSLP) levels in CRSwNP compared to controls. Furthermore, TSLP expression was significantly upregulated from baseline levels following IL-4 or SEB stimulation in type 2 CRSwNP. Notably, IL-4 stimulation led to an increase in oncostatin M (OSM) only in type 2 CRSwNP. Additionally, the number and proportion of TSLP- and OSM-expressing cells among CD163-positive cells were significantly higher in the NP of type 2 CRSwNP patients.Conclusion. NP-derived macrophages from type 2 CRSwNP exhibit elevated expression of TSLP and OSM in response to IL-4 or SEB, potentially contributing to the pathophysiology of type 2 CRSwNP.